Description, distribution and ecology of endemic Tasmanian quillwort, Isoetes jarmaniae, sp. nov. (Isoetaceae; Lycopodiopsida) - Brunton, Daniel F.; Garrett, Michael; Sokoloff, Paul C.; Kantvilas, Gintaras (Phytotaxa, 2021)
Isoetes jarmaniae sp. nov. is described as a new lycophyte endemic to Tasmania, Australia, where it is confined to peat-bound karstic wetlands in several river valleys in the south-west wilderness. While seemingly morphologically closest to I. drummondii, this quillwort has features that are globally uncommon in Isoetes and unknown in other Australasian taxa. Most notable are its markedly flattened, strongly recurved leaves and disproportionately large sporangium ligules that are more suggestive of South American than Australian taxa. As well, the exceptionally thin and wide (alate) megaspore equatorial ridge is swollen at suture intersections, presenting a slightly triangular shape suggestive of the Indian taxon I. udupiensis. The microspores of I. jarmaniae exhibit exceptionally, perhaps uniquely, fine-papillate ornamentation. An original key placing I. jarmaniae in context with the other Tasmanian Isoetes species is provided. This diminutive, apparently diploid species is evidently maintaining a self-sustaining population within a regionally unique habitat and small geographic range.